The study of trivalent-dopants effect on electrical properties of the BaZr0.7In0.3O3-δ system. Issue 195 (2nd January 2019) - Poolphol, Phieraya; Muanghlua, Rangson; Atiwongsangthong, Narin; Vittayakorn, Wanwilai; Vittayakorn, Naratip
Abstract: Perovskite BaZrO3 and BaZr0.7 In0.3 O3-δ (BZI) ceramics were prepared via solid-state reaction. The crystal structure, dielectric and electrical properties of these ceramics were analyzed comparatively. Rietveld analysis indicated that BaZrO3 and BaZr0.7 In0.3 O3-δ (BZI) have cubic symmetry with the Pm 3 ¯ m space group. A small amount of In2 O3 was observed in the BZI ceramic. The lattice parameter ( a ) decreased when a small amount of In 3+ was added. The relative permittivity ε r ( T ) and tan δ ( T ) of BZ and BZI ceramics behaved as plateaus that were independent of frequency and temperature in a temperature range of below 150 ̊C and 50 ̊C, respectively, which ascribed to the intrinsic dielectric properties resulting from electronic and/or ionic polarization. By increasing the temperature further, both ceramics exhibited colossal dielectric constant (CDC) behavior. Conductivity was greater with increasing temperature, which corresponded to Arrhenius behavior. Activation energies were calculated as 0.522 and 0.620 eV for the BZI and BZ system, respectively.